2016
DOI: 10.1038/nmicrobiol.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Endemic hydrothermal vent species identified in the open ocean seed bank

Abstract: Hydrothermal vent systems host microbial communities among which several microorganisms have been considered endemic to this type of habitat. It is still unclear how these organisms colonize geographically distant hydrothermal environments. Based on 16S rRNA gene sequences, we compare the bacterial communities of sixteen Atlantic hydrothermal vent samples with our own and publicly available global open ocean samples. Analysing sequences obtained from 63 million 16S rRNA genes, the genera we could identify in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
7
37
1
Order By: Relevance
“…Similar properties were shown empirically to lead to the spontaneous emergence of the building blocks of life in chemical experiments mimicking earth’s condition at the time of the origin of life22. Such conditions are still found at hydrothermal deep-sea vents, which are discussed as promising candidates for the places of the origin of life23. Further aspects of the PPS (noise tolerance, continuous space, continuous asynchronous motion, local interaction) are furthermore very likely properties for the system in which real life emerged on earth.…”
Section: Discussionsupporting
confidence: 60%
“…Similar properties were shown empirically to lead to the spontaneous emergence of the building blocks of life in chemical experiments mimicking earth’s condition at the time of the origin of life22. Such conditions are still found at hydrothermal deep-sea vents, which are discussed as promising candidates for the places of the origin of life23. Further aspects of the PPS (noise tolerance, continuous space, continuous asynchronous motion, local interaction) are furthermore very likely properties for the system in which real life emerged on earth.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies of diffuse fluid microbiology at hydrothermal vents have focused on the phylogenetic diversity within and between vent fields based on both the 16S rRNA gene as well as specific functional marker genes (e.g., Sievert et al, 1999;Takai et al, 2003;Huber et al, 2007;Opatkiewicz et al, 2009;Huber et al, 2010;Akerman et al, 2013;Perner et al, 2013;Gonnella et al, 2016;Meier et al, 2016). Many studies have analyzed phylogenetic diversity across both space and time, over a range of scales.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have analyzed phylogenetic diversity across both space and time, over a range of scales. For example, a recent analysis of 63 million 16S rRNA gene sequences from ocean water samples and numerous hydrothermal vents along the Mid-Atlantic Ridge concluded that the global ocean acts as a seed bank for hydrothermal systems, with microbial community composition at any individual vent site reflecting both specific environmental parameters as well as random dispersal (Gonnella et al, 2016). In a spatial study of diffuse fluids from five hydrothermally active seamounts along the Mariana Arc, Huber et al (2010) found that while evidence for large-scale geographic differences (> 1000 km) in bacterial community composition existed, at the local scale most vents hosted distinct communities of Epsilonbacteraeota regardless of seamount location.…”
Section: Introductionmentioning
confidence: 99%
“…Models have predicted allopatric speciation at the bacterial strain level in marine systems (Hellweger et al ., ), and limited empirical evidence supports some degree of endemism (Martiny et al ., ; Sul et al ., ; Ryšánek et al ., ). However, there is an emerging consensus that many marine and terrestrial microorganisms – especially abundant taxa – are not dispersal‐limited over evolutionary timescales (Gibbons et al, ; Müller et al ., ; Lynch and Neufeld, ; Girguis, ; Gonnella et al ., ; O'brien et al ., ). Of course, the truth must to lie somewhere in the middle, depending upon the taxonomic, temporal and spatial scales being considered (Foissner, ; Van Der Gast et al ., ; Ryšánek et al ., ).…”
mentioning
confidence: 99%